LITERATURE REVIEW ON CO-FIRING OF SUB BITUMINOUS COAL AND BIOMASS FOR GREENHOUSE GAS EMISSION MITIGATION - Nasution, Rizki Khoiriah (KURVATEK, 2024)
The overuse of fossil fuels has led to global warming and air pollution due to greenhouse gas emissions, particularly CO2. The toxic effects of coal combustion can be reduced by mixing coal with biomass, which is called the co-firing method. This study aims to analyze the use of co-firing using various types of biomass based on previous studies. The results show that different biomass blending ratios affect the emission reduction significantly. Mixing palm kernel shell biomass at a ratio of 10% biomass and 90% coal reduced emissions by 20%, while mixing mesua ferrea tree biomass and sawdust at a ratio of 75% coal and 25% biomass reduced emissions by 45%. The use of empty fruit bunch biomass at a ratio of 30% biomass and 70% coal can reduce CO2 emissions by 72.14%. Overall, co-firing proved effective in reducing greenhouse gas emissions and accelerating the transition to renewable energy, although its effectiveness depends on the type of biomass and the blending ratio.